Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T22:23:05+01:00
(4m *0,2m)*2m=1,6m ^{2}*0,3m=0,48m ^{3}

3m-0,2m-0,2m=2,6m-II bok
(2,6m*0,2m)*2m=1,04m ^(2)*0,3m= 0,3m^(3)
Odp: Zużyto 0,8m sześciennego.
2009-11-26T22:50:34+01:00
A)
[(6a+7)/7] - 3 = (5a - 3)/8 /*56
(56/7)*(6a+7) - 3*56 = (56/8)*(5a - 3)
8*(6a+7) -168 = 7*(5a - 3)
48a + 56 - 168 = 35a - 21
13a = 91 /: 13
a = 7
b)
(b - 4)/5 = 9 - [(2b - 41)/9] /*45
(45/5)*(b - 4) = 9*45 - (45/9)*(2b - 41)
9*(b - 4) = 405 - 5*(2b - 41)
9b - 36 = 405 - 10b + 205
19b = 646 /:19
b = 34
c)
10 - [(3c - 1)/2] = (6c + 3)/11 /*22
22*10 - (22/2)*(3c - 1) = (22/11)*(6c + 3)
220 - 11*(3c - 1) = 2*(6c + 3)
220 - 33c + 11 = 12c + 6
225 = 45c /:45
c = 5
d)
2 - [(3a - 7)/4] + [(a + 17)/5] = 0 /*20
20*2 - (20/4)*(3a - 7) + (20/5)*(a + 17) = 0
40 - 5*(3a - 7) + 4*(a + 17) = 0
40 - 15a + 35 + 4a + 68 = 0
-11a = -143 /:(-11)
a = 13
e)
[(b+6)/2] + [(5 - 4b)/3] = (8 - b)/6 /*6
(6/2)*(b+6) + (6/3)*(5 - 4b) = (6/6)*(8 - b)
3*(b+6) + 2*(5 - 4b) = 8 - b
3b + 18 + 10 - 8b = 8 - b
-4b = -20 /:(-4)
b = 5
f)
[(9c + 7 - 2c)/2] + (c - 2)/7 = 36
[(7c + 7)/2] + (c - 2)/7 = 36 /*14
(14/2)*(7c + 7) + (14/7)*(c - 2) = 504
7*(7c + 7) + 2*(c - 2) = 504
49c + 49 + 2c - 4 = 504
51c = 459 /:51
c = 9